Akses Pendidikan Bagi Perempuan di Tengah Belenggu Patriarki Kota Bandung - Najwa Nuraeni; Rini Sulastri (Gunung Djati Conference Series, 2024)
This study discusses gender and education. In the field of education, women have always been subordinated, because women are always considered inferior (weak) and men are superior (strong). In education, there is no reason to discriminate against each other between men and women. There are four things identified from this study (1) The context of access to women's education, (2) the form of access to women's education, (3) the patriarchal context of women's access to education, (4) the form of patriarchy and stereotypes in women's access to education. This research uses Marxist conflict theory which states that gender injustice is not due to biological factors, but because of oppression from superior to inferior. Data analysis in this study was carried out during the interview process. Interviews were conducted by researchers on 3 female students in grade 12. The method used in this study is a descriptive qualitative method to describe the results of the analysis in more depth. The conclusion in this study is that there is still a patriarchal system that parents teach their daughters, in order to submit to every speech or command of men.